Exams and notes (Journal of Parents and Teachers, 2024)
The article encourages reflection on whether the exams administered truly serve a purpose and whether students learn from them. Socrates was an advocate for teaching without turning exams into a source of frustration for his students; instead, he invited them to reflect on life rather than becoming test-taking machines.
Keywords: Socrates; exams; usefulness; teaching